Losartan Preserves Erectile Function by Suppression of Apoptosis and Fibrosis of Corpus Cavernosum and Corporal Veno-Occlusive Dysfunction in Diabetic Rats - Wen Ji Li; Mingxi Xu; Meng Gu; Da-chao Zheng; Jianhua Guo; Zhikang Cai; Zhong Wang (Cellular Physiology and Biochemistry, 2017)
Background/Aims: Transforming growth factor-β1 (TGF-β1) plays important roles in penile corporal fibrosis and veno-occlusive dysfunction (CVOD). Angiotensin II (Ang II) is critically involved in erectile dysfunction, and blocking of Ang II is more important than inhibition of TGF-β in non-penile tissue fibrosis. However, the role of Ang II in corporal fbrosis and CVOD in a diabetic condition has not been investigated. Methods: Diabetic rats were treated with sildenafil or losartan (an Ang II antagonist) alone or in combination. Intracavernosal pressure, dynamic infusion cavernosometry, and histological and molecular alterations of the corpus cavernosum were examined. Results: Diabetic rats exhibited decreases in erectile response, severe CVOD, apoptosis, fibrosis, and activation of the TGF-β1 pathway. Treatment with sildenafil had a modest effect on erectile response and an insignificant suppressive effect on CVOD, apoptosis, fibrosis, and the TGF-β1 pathway. Although losartan greatly improved the histological and molecular changes and CVOD as compared with sildenafil, its effect on erectile response was low. The combination of sildenafil and losartan had superior effects on these parameters than did either compound alone. Conclusion: Ang II activation may be involved in apoptosis and fibrosis of the corpus cavernosum through Smad and non-Smad pathways, resulting in CVOD and ED. The low efficacy of sildenafil in a diabetic ED rat model was at least partly due to its inadequate effects on apoptosis, fibrosis, and CVOD.